KERJASAMA INDONESIA DAN TAIWAN (STUDI KASUS : MOROTAI DEVELOPMENT PROJECT) - Joice Victory Bakara; Tri Joko Waluyo (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research aims to find out the relationship of cooperation between Indonesia and Taiwan in Morotai Development Project that is focused on the factors behind Indonesia in cooperation with Taiwan. Morotai island is the name of an island as well as a name of a new district in the province of North Maluku. Morotai island is a strategic region that has avariety of potential especially tourism and fisheries. In 2014 through government regulation, Morotai established as one of Special Economic Zone in Indonesia. The result indicate that the cooperation between Indonesia and Taiwan in Morotai Development Projects due to the interest of each circle to benefit from the potential of Morotai as Special Economic Zones in Indonesia. Indonesia in cooperation with Taiwan due to Indonesian interests in the construction and infrastructure development, the potential of fisheries and tourism potential of MorotaiKeywords : cooperation, Indonesia and Taiwan, interdependence, Morotai Development Project, Special Economic Zone ( SEZ )